Identification of N(6)-methyladenosine reader proteins - Zhou, Katherine I. (Methods, 2017)
The reversible N(6)-methyladenosine (m(6)A) modification of eukaryotic messenger RNAs (mRNAs) is a widespread regulatory mechanism that impacts every step in the mRNA life cycle. The effect of m(6)A on mRNA fate depends on the binding of “m(6)A reader” proteins – RNA binding proteins that specifically bind to RNAs containing m(6)A. Here, we describe an RNA pull-down method that can be used to identify novel m(6)A reader proteins starting from a known m(6)A-modified site in cellular or viral RNA. We further describe how a combination of immunoprecipitation-based sequencing methods can be used to identify m(6)A-modified sites bound by an m(6)A reader protein on a transcriptome-wide level. The discovery of new m(6)A reader proteins and their m(6)A-modified targets would provide further insight into the mechanisms and functions of m(6)A in the cell.